2000
DOI: 10.1055/s-2000-7976
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Clozapine and Olanzapine on the EEG in Patients with Schizophrenia

Abstract: Clozapine is known to induce epileptic seizures and changes in EEG-patterns, including slowing and the appearance of epileptiform activity. Olanzapine, a new antipsychotic drug, shares many pharmacological and clinical properties with clozapine. However, in patients treated with olanzapine, no case of seizure induction has been reported so far, and the EEG has not been studied systematically. We examined the EEGs of patients with schizophrenia treated with either olanzapine (N = 9) or clozapine (N = 9) prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It was also observed that EEG abnormalities were statistically significantly increased with dose in the olanzapine group [7]. In another study, a proportion of 44% of patients with EEG abnormalities under olanzapine treatment was described; however, this was based on a small sample size ( n  = 9 in [15]). The proportion of EEG abnormalities in a study by Centorrino et al [6] was also comparable (38.5%).…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that EEG abnormalities were statistically significantly increased with dose in the olanzapine group [7]. In another study, a proportion of 44% of patients with EEG abnormalities under olanzapine treatment was described; however, this was based on a small sample size ( n  = 9 in [15]). The proportion of EEG abnormalities in a study by Centorrino et al [6] was also comparable (38.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with AE will need antipsychotics to control agitation and psychosis. 1 One option is to avoid agents that lower seizure threshold (eg, clozapine and olanzapine) 2 in patients with seizures or who are at increased seizure risk (eg, patients with limbic or cortical encephalitis or who have lateralised periodic discharges (LPDs) on electroencephalogram (EEG)). Antipsychotics that prolong the QT interval (eg, ziprasidone and IV haloperidol) should be used with caution or avoided in dysautonomic patients with symptomatic bradycardia or heart block.…”
Section: Introductionmentioning
confidence: 99%
“…Olanzapine is known to cause highest EEG changes, in 35-45% of cases,[ 6 7 8 9 ] among the non-Clozapine newer antipsychotics. [ 6 7 8 9 ] Atypicals have high propensity to cause EEG changes compared to typical antipsychotics. [ 10 ] Generalized/focal symmetrical theta and delta waves are more commonly found abnormal activities followed by asymmetrical slow waves, sharp waves with phase reversals, and spike-and-slow wave patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The later severe epileptic changes were noted in up to 11-15% of cases on Olanzapine. [ 4 8 9 ] EEG changes were noted at around 4-7 months of starting Olanzapine in most of the literature. [ 1 2 8 ] As abnormal EEG could be seen in most of the reported cases including our case, it would be seen beneficial to monitor EEG as a seizure preventive strategy in high-risk patients after the cost effectiveness being evaluated.…”
Section: Discussionmentioning
confidence: 99%